2016
DOI: 10.1590/0001-3765201620150345
|View full text |Cite
|
Sign up to set email alerts
|

What the largest tadpole feeds on? A detailed analysis of the diet composition of Pseudis minuta tadpoles (Hylidae, Dendropsophini)

Abstract: We analyzed the diet of 25 individuals of Pseudis minuta tadpoles which consisted in debris with more than 30%, follow by diatoms, euglenids, green algae, and desmids. With regard to the feeding strategy, P. minuta tadpoles are generalist consumer. The negative correlation between the abundance of items in the digestive tract and the mouth width indicate an effect of metamorphosis on the diet. key words: algae, anuran, metamorphosis, trophic ecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…We noticed the filamentous green algae Mougeotia to be most consumed by tadpoles of both stages in the middle of the wet season and at the onset of the dry season. Mougeotia was present in large amounts in the diet of B. saxicola tadpoles (present study) and has been detected in the diets of tadpoles of other species as well (Dickman, 1968;Huckembeck et al, 2016), despite having low nutritional value (Kupferberg et al, 1994).…”
Section: Discussionsupporting
confidence: 57%
“…We noticed the filamentous green algae Mougeotia to be most consumed by tadpoles of both stages in the middle of the wet season and at the onset of the dry season. Mougeotia was present in large amounts in the diet of B. saxicola tadpoles (present study) and has been detected in the diets of tadpoles of other species as well (Dickman, 1968;Huckembeck et al, 2016), despite having low nutritional value (Kupferberg et al, 1994).…”
Section: Discussionsupporting
confidence: 57%
“…Diatoms (Bacillariophyceae) were one of the most important items in the tadpole diet of the five species examined in this study. They have also been cited as the most frequently consumed item in the diets of other tadpoles of lotic (Santos et al, 2016) and lentic (Rossa-Feres et al, 2004;Echeverría et al, 2007;Bionda et al, 2012;Huckembeck et al, 2016) environments, indicating that high levels of diatoms in intestinal contents of tadpoles can be considered a general phenomenon. This information is relevant to studies examining the food preferences of anurans and environmental monitoring, including studies that evaluate the presence or absence of certain diatomaceous groups, which can be considered indicators of environmental quality (Cejudo-Figueiras et al, 2010;Antón-Garrido et al, 2013 Other items found in the diet of the tadpoles examined were plant fragments, protozoa, fungi and animal parts.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have a limited understanding of the trophic ecology of anuran larvae in comparison with adult forms. This is partly due to the lack of studies regarding the food habits of tadpoles, which has hindered our ability to fully understand the natural history of the species and its functional role in the environment throughout the tadpole phase (Huckembeck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Las 83 larvas de Spea multiplicata, representan un tamaño de muestra superior a otros estudios que han analizado la dieta de renacuajos de otras especies. Por ejemplo, Arias et al, (2002) solo estudiaron 10 larvas de Pseudis paradoxa (Hyldiae), Deepthi et al, (2007) emplearon 40 larvas de Nannophrys ceylonensis (Dicroglossidae), Bionda et al, (2013) trabajaron con 57 larvas de Rana sauterii (Ranidae) y Bufo bankorensis (Bufonidae) y Huckembeck et al, (2015) utilizaron 16 larvas de Phisalemus biligonigerus y 25 larvas de Pseudis minuta (Hylidae). Además, en este trabajo se abarcó la mayor parte de los estadios de las larvas con movilidad, mientras que en el resto de los trabajos sólo abarcaron unas cuantas etapas del índice de Gosner (1960).…”
Section: D) Variación Morfométrica Y Dieta De Las Larvas De Spea Multunclassified
“…La dieta de las larvas de Spea multiplicata en Zaachila, Oaxaca, estuvo compuesta principalmente por microalgas, detritus y restos de origen vegetal, resultados que coinciden con los reportado para la mayoría de las especies de anuros (Arias et al, 2002;Altig et al, 2007Huckembeck et al, 2015, por lo tanto puede considerarse a Spea multiplicata un fitófago.…”
Section: D) Variación Morfométrica Y Dieta De Las Larvas De Spea Multunclassified